MicroRNAs as genetic sculptors: fishing for clues - Takacs, Carter M. (2010)
microRNAs (miRNA) encode small RNA molecules of ~22nts in length that regulate the deadenylation, translation, and decay of their target mRNAs. The identification of miRNAs in plants and animals has uncovered a new layer of gene regulation with important implications for development, cellular homeostasis and disease. Because each miRNA is predicted to regulate several hundred genes, a major challenge in the field remains to elucidate the precise roles for each miRNA and to understand the physiological relevance of individual miRNA-target interactions in vivo. Despite the wide variety of biological contexts where miRNAs function, a common theme emerges, whereby miRNAs shape gene expression within both spatial and temporal dimensions by removing messages from previous cellular states as well as modulating the levels of actively transcribed genes. This review will focus on the role that the teleost Danio rerio (zebrafish) has played in shaping our understanding of miRNA function in vertebrates.